Lean model applied to increase the order fulfillment in SMEs in the footwear industry - Laura-Ulloa, Guillermo André (2022)
Over the last few years, the Peruvian footwear industry has been affected by the increase in imports, mainly from China, with an FOB value that has risen to 516 million dollars, generating a deficit in the trade balance and forcing producers to become more competitive. Therefore, the national industry seeks to raise the standards of productivity and quality of its products, increasing the service level offered. In this research, it is proposed an improvement model that allows optimizing order fulfillment, which integrates lean manufacturing tools, including 5S, line balancing, and standardized work. After the implementation of the model, the cycle time will be reduced by 27.27%, the number of defective products in the assembly area will decrease by 8. 90%, and in the flooring area by 19.91%. Due to this, it is possible to increase the value of OTIF by 44.48%.